2005
DOI: 10.1002/ana.20700
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological characterization of progressive aphasia

Abstract: Progressive aphasia is best seen as a composite of two conditions, on both clinical and pathological levels: progressive nonfluent aphasia and semantic dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
272
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(290 citation statements)
references
References 76 publications
11
272
2
5
Order By: Relevance
“…However, recent articles have demonstrated that focal, atypical distribution of Alzheimer disease (AD) pathology is responsible for 20% to 30% of cases with various forms of PPA. 2,[33][34][35] Retrospective PET and MRI studies 36,37 demonstrated in PPA patients with AD pathology a pattern of temporoparietal involvement similar to LPA. Furthermore, all US patients described in this article had cortical amyloid binding on PET scans using the Pittsburgh compound B tracer.…”
Section: Verbal Response Pointingmentioning
confidence: 99%
“…However, recent articles have demonstrated that focal, atypical distribution of Alzheimer disease (AD) pathology is responsible for 20% to 30% of cases with various forms of PPA. 2,[33][34][35] Retrospective PET and MRI studies 36,37 demonstrated in PPA patients with AD pathology a pattern of temporoparietal involvement similar to LPA. Furthermore, all US patients described in this article had cortical amyloid binding on PET scans using the Pittsburgh compound B tracer.…”
Section: Verbal Response Pointingmentioning
confidence: 99%
“…As many as one third of patients diagnosed clinically as either progressive non-Xuent aphasia (PNFA) or semantic dementia showed this pattern [36]. Some reports have remarked the relative sparing of medial temporal lobe structures (hippocampus and entorhinal cortex) [16,17,56].…”
Section: Introductionmentioning
confidence: 99%
“…There are established associations between semantic-variant PPA (svPPA) and frontotemporal lobar degeneration-TAR DNA binding protein 43 (TDP-43); nonfluentvariant PPA (nfvPPA) and frontotemporal lobar degeneration-tau; and logopenic-variant PPA (lvPPA) and Alzheimer pathology. [1][2][3][4][5] The recommendations on clinical subtyping of PPA have proposed that clinical classification can be supported by imaging according to the pattern of regional atrophy or metabolic impairment. 6 Left posterior frontoinsular atrophy in nfvPPA, anterior temporal atrophy in svPPA, and left posterior peri-Sylvian or parietal atrophy in lvPPA are the recommended atrophy patterns.…”
mentioning
confidence: 99%